2011
DOI: 10.1001/archophthalmol.2011.313
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Halo Nevi Following Plaque Radiotherapy for Uveal Melanoma

Abstract: while others have not. 4,5 None of these reports had clinical evidence of choroidal involvement. The vitelliform lesions have been postulated to represent a new paraneoplastic clinical manifestation. The pathologic results in this case argue against a paraneoplastic entity but may suggest a local metastatic cause with subclinical choroidal involvement. Another explanation is that choroidal involvement occurred after the vitelliform lesions with the dissemination of the metastatic melanoma. Further studies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…A recent study demonstrated that after brachytherapy, IL-1β, IL-6, and IL-8 increase in the aqueous humor; levels of IL-6 and IL-8 were positively associated with scleral surface radiation dose (24). Similar to reports of depigmentation after external beam radiotherapy for cutaneous melanoma described above, investigators recently described a 28 year-old woman who developed halo depigmentation around cutaneous nevi 2 months after plaque brachytherapy for choroidal melanoma (25). …”
Section: Introductionmentioning
confidence: 53%
“…A recent study demonstrated that after brachytherapy, IL-1β, IL-6, and IL-8 increase in the aqueous humor; levels of IL-6 and IL-8 were positively associated with scleral surface radiation dose (24). Similar to reports of depigmentation after external beam radiotherapy for cutaneous melanoma described above, investigators recently described a 28 year-old woman who developed halo depigmentation around cutaneous nevi 2 months after plaque brachytherapy for choroidal melanoma (25). …”
Section: Introductionmentioning
confidence: 53%
“…It is speculated that declining host defense mechanism with advancing age might contribute to poor prognosis of older patients with cutaneous melanoma (24). It is unclear if this is relevant for uveal melanoma, but there is clinical evidence of systemic immune stimulation in patients with uveal melanoma manifesting as cutaneous depigmentation (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, UMs treated with eye plaques also demonstrated an increase in immune response, by expression of tumor antibodies [14-15]. Also, few case reports suggest a potential systemic effect related to brachytherapy in patients with choroidal melanoma [16]. Preclinical studies have proposed that brachytherapy may induce a similar increase in Fas expression to induce an abscopal response [17].…”
Section: Reviewmentioning
confidence: 99%